Pelaksanaan Pelatihan Metodologi Penelitian Sosial Untuk Memahami Fenomena Sosial Kemiskinan Perkotaan Bersama Serikat Perjuangan Rakyat Indonesia (SPRI) Jakarta Barat - Puspita , Ratna; Polimpung, Hizkia Yosias; Irfansyah, Azhar; Arifianto, M Lukman; Prasojo, Prasojo (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
In the process of thinking, humans need a methodology as a guide to be orderly and directed. Likewise in understanding social phenomena. For ordinary people, social phenomena are seen as a daily reality. For researchers, behind a social phenomenon there is a discrepancy between the ideal concept and reality. This community service activity was carried out to provide training to the Indonesian People's Struggle Union – Serikat Perjuangan Rakyat Indonesia (SPRI). SPRI as a non-profit organization that focuses on urban poverty issues requires a way to use research methodologies in a short, fast and precise way in understanding and finding solutions to poverty problems in the capital city of Jakarta. This training is carried out by providing material ranging from the basic understanding of research to the process of using the preparation of research methodologies to support the tasks of SPRI.